Protein diffusion characteristics in the hydrogels of poly(ethylene glycol) and zwitterionic poly(sulfobetaine methacrylate) (pSBMA). (August 2016) - Wu, Jiang; Xiao, Zecong; He, Chaochao; Zhu, Jingjing; Ma, Guanglong; Wang, Guangzhi; Zhang, Hongyu; Xiao, Jian; Chen, Shengfu
Graphical abstract: Abstract: Nonfouling materials such as neutral poly(ethylene glycol) (PEG) and zwitterionic poly(sulfobetaine methacrylate) (pSBMA) are ideal biocompatible materials for drug, especially protein drug delivery. The interaction behavior of protein between the nonfouling materials could cause great impact on their future applications, such as controlled release drug delivery systems. In this work, we investigated the diffusion behavior of the fluorescence-labeled model proteins (bovine serum albumin (BSA) and lysozyme (LYZ)) in nonfouling PEG, pSBMA and mixed PEG-SBMA hydrogels (SBMA:PEG 4:1, SBMA:PEG 1:4). It was observed that these four hydrogels showed varied diffusion behavior for either negatively charged BSA or positively charged LYZ due to protein-polymer interaction and the free water content in hydrogel matrix. The relatively stronger interaction between protein-PEG than protein-pSBMA could increase protein loading efficiency and control release rate by changing ratio of PEG to SBMA in the hybrid hydrogel. Moreover, it is further demonstrated the free water (freezable water) content in low cross-linked hydrogel, not the equilibrium water content (EWC), is a more accurate parameter to reflect the diffusion behavior of protein molecules. Thus, these results together provide new insights of the interactions between protein molecules and nonfouling polymers as well as the bio applications of the nonfouling polymeric hydrogels. Statement of Significance: This work shows that the relative stronger interaction between protein-PEG than protein-pSBMA could increase protein loading efficiency and control release rate by the change ratio of PEG to SBMA in the hydrogel, while the free water (freezable water) content in low cross-linked hydrogel, not the equilibrium water content (EWC), is a more accurate parameter to reflect the diffusion behavior of protein molecules. The impact of this work (i) gains some new insights of the interactions between protein molecules and nonfouling polymer matrixes for protein drug delivery; (ii) prompts to apply the weak PEG-protein interactions to protein drug loading and release; (iii) provides a new fundamental understanding of free water in hydrogel for protein diffusion.